Physical and morphometric characterization of Frieswal cattle - Gaur, G K; Kumar, Arun; Singh, Umesh; Rathi, S K; Singh, Kripal; Biswas, B B (The Indian Journal of Animal Sciences, 2011)
The present investigation was undertaken to study the physical and morphometric characteristics in Frieswal cattle. The data pertained to 809 FrieswaI animals ofdifferent cat~ories. The physical characteristics included colour pattern of body, skin, tail switch, muzzle and hoof, length/size of tail, body, dewlap, naval flap, shape/size of udder/teat and udder appearance. Heart girth, body length and height and weights at different stages were taken up for morphometric characterization. The main body colour of Frieswal animals, was black and white (32% cows and 34% heifers) in different proportions varying from 10 to 90%. Skin colOti~ in majority of animals was black (53% cows and 48% heifers) followed by black and brown (36% cows and 46% helifers). The prominent colour oftail switch was white (47% cows and 35% heifers). Most of the animals had black muzzle (90% cows and 96% heifers). Hoofcolour was black in 57% cows and 59% heifers. Adult Frieswal cows were medium (39%) to large in size (56%) with medium dewlap (87%) and small naval flap (93%). Most ofthe animals were docile (83%). Udder was symmetrical in most ofthe cows (90%) and heifers (100%). Frieswal calves averaged 26.51 kg at birth, 66.69 kg at 3 months and 117.95 kg at 6 months of age. The body weight of the heifers was 257 kg at 18 month and 323 kg at 24 month of age. Weight at first calving averaged 412 kg. Body height, body length and heart girth averaged 122, 122 and 161 em in heifers; 129, 122 and 184 em in adult cows and 142, 148 and 208 cm in bulls.Â